Analisis Cyberbullying: Komentar Kebencian Terhadap Pembuat Konten Beauty Influencer di Media Sosial Tiktok - Arsyinda Fitri Maharani; Chazizah Gusnita (Dinasti Research, 2024)
This research discusses cyberbullying in the form of hate comments that befell beauty influencers on Tiktok social media. The phenomenon of cyberbullying and hate speech often occurs on social media and affects content creators, with the aim of convincing, hurting and intimidating someone with the comments they make. The theory used in this research is Routine Activity Theory put forward by Cohen & Felson. According to Cohen & Felson, crime can occur due to 3 factors, namely a motivated perpetrator: a motivated perpetrator, a suitable target: the presence of a suitable target, and a capable guardian: the absence of a guard or supervisor to protect the victim from criminal acts. Data collection techniques were carried out in three ways, namely observation, interviews and literature review. The purpose of this writing is to provide knowledge to readers about the problem of cyberbullying and hate speech and what impacts the victims feel after receiving these hate comments. The results of this research show that the daily routine activities carried out by beauty influencers on social media, both for their work and social life, are vulnerable to making them victims of cyberbullying in the form of hate speech. The hate speech they receive makes them mentally down, making them feel stressed and useless. And the reason the perpetrators make comments like that is because they are motivated by the content from beauty influencers that they see and it creates a feeling of dislike in them.